2012
DOI: 10.1002/app.36588
|View full text |Cite
|
Sign up to set email alerts
|

Microwave preparation and properties of O‐crosslinked maleic acyl chitosan adsorbent for Pb2+ and Cu2+

Abstract: A novel chitosan-based adsorbent (CCTM) was prepared by the reaction of epichlorohydrin O-crosslinked chitosan with maleic anhydride under microwave irradiation. The chemical structure of this polymer was characterized by infrared spectroscopy and X-ray diffraction analyses. The effects of various variables such as degree of substitution, adsorption time, initial metal ion concentration, solution pH, and temperature, on the adsorption of Pb 2þ and Cu 2þ by CCTM were investigated. The results demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The XRD pattern of chitosan in this study displayed two sharp diffraction peaks at 2 θ = 10° and 20°, revealing the high crystallinity of chitosan. This result is consistent with the result of a number of previous studies [22,32,33], which reported the typical X-ray diffraction pattern of chitosan. The high crystallinity is due to the chitosan structure while plenty of hydroxyl and amino groups could form strong intermolecular and intramolecular hydrogen bonds [33].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The XRD pattern of chitosan in this study displayed two sharp diffraction peaks at 2 θ = 10° and 20°, revealing the high crystallinity of chitosan. This result is consistent with the result of a number of previous studies [22,32,33], which reported the typical X-ray diffraction pattern of chitosan. The high crystallinity is due to the chitosan structure while plenty of hydroxyl and amino groups could form strong intermolecular and intramolecular hydrogen bonds [33].…”
Section: Resultssupporting
confidence: 93%
“…The XRD measurements of chitosan and CLCG were recorded as described by Ge et al [22] and Zhang et al [59] by using an XPert PRO diffractometer (Holland) with a detector operating under a voltage of 40.0 kV and a current of 30.0 mA using CuKo radiation. The recording range of 2 θ was 5° to 60°, and the scanning speed was 6°/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 10 was assigned to the crystal form I and the strong peak at 20 was assigned to form II [51]. This is because the structure of chitosan molecules has certain regularity which can form crystalline regions very easily [52]. But, for succinated chitosan, the peak at 10 disappears and the reflection at 20 also significantly decreases [53].…”
Section: Determination Of Shell-crosslinked Structurementioning
confidence: 99%
“…The linear forms of pseudo-first-order and the pseudo-second-order 226 equations are expressed as follows(Ge, Chen, & Huang, 2012):…”
mentioning
confidence: 99%